Analyses of noncommensurate sampling used in high-precision regenerative pseudo-noise ranging systems - Xu, Zhao-bin; Jin, Xiao-jun; Zhang, Chao-jie; Jin, Zhong-he (Journal of Central South University, 2014)
A high-precision pseudo-noise ranging system is often required in satellite-formation missions. But in an actual PN ranging system, digital signal processing limits the ranging accuracy, only level up with meter-scale. Using non-integer chip to sample time ratio, noncommensurate sampling was seen as an effective solution to cope with the drawback of digital effects. However, researchers only paid attention to selecting specific ratios or giving a simulation model to verify the effectiveness of the noncommensurate ratios. A qualitative analysis model is proposed to characterize the relationship between the range accuracy and the noncommensurate sampling parameters. Moreover, a method is also presented which can be used to choose the noncommensurate ratio and the correlation length to get higher phase delay distinguishability and lower range jitter. The simulation results indicate the correctness of our analyses and the optimal ranging accuracy can be up to centimeter-level with the proposed approach.